Leukocytoclastic vasculitis: A window to systemic Churg Strauss syndrome - Sudhir V Medhekar; Resham J Vasani; Ratnakar R Kamath (Wolters Kluwer Medknow Publications, 2012)
A twenty year old male presented with purpuric lesions with chronic painful ulcers over the lower extremities and a recurrent pruritic rash on the trunk for 10 years. He was diagnosed as idiopathic leukocytoclastic vasculitis (LCV) after investigations failed to reveal a systemic association. He was treated with immunosuppressants at each visit with partial remission. In 2004, he was diagnosed with bronchial asthma and allergic rhinitis. In his recent admission, he showed necrotic ulcers on legs and extensive shiny, truncal micropapules. Examination revealed maxillary sinus tenderness and loss of sensation on the medial aspect of the left lower limb. Biopsy of ulcer and the micropapules showed the presence of extravascular eosinophils, while hematological investigations showed peripheral eosinophilia of 18%, raised serum Immunoglobulin E (IgE), Anti nuclear antibody (ANA) positivity and negative antineutrophil cytoplasmic antibody (ANCA). Radiography confirmed maxillary sinusitis, nerve conduction studies revealed mononeuritis of the anterior tibial nerve and pulmonary function tests (PFT) were normal. Clinical examination and investigations pointed towards the diagnosis of Churg-Strauss syndrome (CSS). This report highlights the development of full-blown CSS over a period of 12 years in a patient initially diagnosed as idiopathic LCV, emphasizing the need for regular follow-up of resistant and recurrent cases of LCV.